Evaluation of Diverse G. arboreum Genotypes under High Density Planting System on Rainfed Vertisols for Earliness, Productivity and Fibre Quality - VENUGOPALAN, M. V.; BLAISE, D.; LAKDE, SHUBHANGI (Cotton Research Journal, 2021)
Seventeen G. arboreum genotypes developed at diverse locations across India were evaluated under High Density Planting System (HDPS) at 60x10 cm spacing during the kharif (monsoon) season of 2016-17 and 2017-18, at the research farm of ICAR-Central Institute for Cotton Research, Nagpur under rainfed conditions on Vetisols. The objective was to identify high yielding, early maturing and compact genotypes with good fibre quality for promotion through HDPS under rainfed conditions. The genotypes PA 08, PA 760, G Cot 19, TKA 9102/3, DLSa 17, PA 812 and PA 785 were at par with the check BG II hybrid Ajeet 155 with reference to earliness in terms of days to flowering. Under HDPS, four genotypes genotypes- PA 785, PA 812, PA 740 and G.Cot-19 produced significantly higher yield than the check hybrid Ajeet 155 Bt planted at recommended spacing of 90x60 cm. Genotypes PA 760, PA 740, PA 812 and PA 785 possessed fibre quality parameters comparable to the currently available BG II hybrid Ajeet 155. The high values of Spinning Consistency Index (129-145) in these genotypes reiterate their ability to produce yarn of high strength. Both, days to first open flower and days to first open boll could be used as reliable traits to screen for earliness in G. arboreum cultures.